1980
DOI: 10.1002/1097-0142(19800215)45:4<647::aid-cncr2820450405>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiation therapy in the management of plasma cell tumors

Abstract: A retrospective review is reported of 128 patients presenting with multiple myeloma and 16 patients presenting with solitary plasmacytoma. Ninety-one percent of 116 evaluable patients treated for palliation of painful bone disease received some degree of subjective pain relief. The radiation dose most frequently prescribed was between 1500 and 2000 rad. Of the 278 ports treated, only 17 (6.1%) were re-treated to the same area at a later date. There was no increase in incidence of re-treatment with lower radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
7

Year Published

1981
1981
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 16 publications
3
69
1
7
Order By: Relevance
“…This finding is in contrast to the study by Mill and Griffith, who reported better local control rates among patients who received >50 Gy, 17 and the findings of Tournier-Rangeard et al, who reported that doses 45 Gy improved local control among patients with extramedullary SP. 18 Similarly, Mendenhall and colleagues reported that radiation doses 40 Gy resulted in a local control rate of 94% compared with 69% in patients who received <40 Gy.…”
Section: Discussioncontrasting
confidence: 94%
“…This finding is in contrast to the study by Mill and Griffith, who reported better local control rates among patients who received >50 Gy, 17 and the findings of Tournier-Rangeard et al, who reported that doses 45 Gy improved local control among patients with extramedullary SP. 18 Similarly, Mendenhall and colleagues reported that radiation doses 40 Gy resulted in a local control rate of 94% compared with 69% in patients who received <40 Gy.…”
Section: Discussioncontrasting
confidence: 94%
“…Fugwe 2 Overall survival ( ) and disease-free survival (-) for the ten patients with extramedullary plasmacytoma. (Kotner and Wang, 1972;Meyer and Schulz, 1974;Corwin and lindberg, 1979;Woodruff et al, 1979ab;Mill et al, 1980;Mendenhall et al, 1980;Harwood et al, 1981;Bush et al, 1981;Knowling et al, 1983;Greenberg et al, 1987;Frssica et al, 1989), whereas others have found that local failure can occur with doses greater than 6000 cGy in patients with EMP (Petrovich et al, 1977;Bush et al, 1981). Mendenhall et al (1980) (Knowling et al, 1983;Mayr et al, 1990 (Mayr et al, 1990;Jackson and Scarffe, 1990;Holland et al, 1992).…”
Section: Clinical Investigationmentioning
confidence: 99%
“…The tumors may be either small or discrete, or they may grow to large dimensions. These lesions have a greater tendency to expand locally rather than to disseminate, a property that may be controlled by specific cytokines (Mill et al, 1980). The bone is probably the site of origin; however, they may arise from mucosa contained within the sphenoid and petrous bones, since non-osseous myelomas are common.…”
mentioning
confidence: 99%